Pseudomonas oligotrophica sp. nov., a Novel Denitrifying Bacterium Possessing Nitrogen Removal Capability Under Low Carbon–Nitrogen Ratio Condition - Zhang, Mingxia; Li, Anzhang; Yao, Qing; Xiao, Botao; Zhu, Honghui (Frontiers in Microbiology, 2022)
Pseudomonas is a large and diverse genus within the Gammaproteobacteria known for its important ecological role in the environment. These bacteria exhibit versatile features of which the ability of heterotrophic nitrification and aerobic denitrification can be applied for nitrogen removal from the wastewater. A novel denitrifying bacterium, designated JM10B5aT, was isolated from the pond water for juvenile Litopenaeus vannamei. The phylogenetic, genomic, physiological and biochemical analyses illustrated that the strain JM10B5aT represented a novel species of the genus Pseudomonas, for which the name Pseudomonas oligotrophica sp. nov. was proposed. The effects of carbon sources and C/N ratios on denitrification performance of strain JM10B5aT were investigated. And the results revealed that sodium acetate was selected as the optimum carbon source for denitrification of this strain. Besides, strain JM10B5aT could exhibit complete nitrate removal at the low carbon-nitrogen ratio of 3. Genomic analyses revealed that JM10B5aT possessed the functional genes including napA, narG, nirS, norB and nosZ, which might participate in the complete denitrification process. Comparative genomic analyses indicated that many genes related to aggregation, utilization of alkylphosphonate and tricarballylate, biosynthesis of cofactors and vitamins were contained in the genome of strain JM10B5aT. These genomic features were indicative of its adaption to various niches. Moreover, strain JM10B5aT harbored the complete operons required for the biosynthesis of vibrioferrin, a siderophore, which might be conducive to the high denitrification efficiency of denitrifying bacterium at low C/N ratio. Our findings demonstrated that the strain JM10B5aT could be a promising candidate for treating wastewater with a low C/N ratio.